Fluorescent Paints in Contemporary Murals: A Case Study - Francesca Sabatini; Jacopo La Nasa; Ilaria Degano; Beatrice Campanella; Stefano Legnaioli; Ilaria Saccani; Francesca Modugno (Heritage, 2023)
Recently, a notable change has occurred in how street art murals are perceived by art history and the general public, with a growing recognition of their social and cultural significance and a new focus on preserving the most representative modern urban murals for future generations. An interesting case study is constituted by the “UBUNTU” mural (Ivan Pontevia and Daniele Castagnetti, Reggio Emilia, 2018), whose appearance has radically changed in a few years. Indeed, the intense and direct exposure to sunlight as well as the environmental and polluting agents have induced the bleaching and fading of the original highly fluorescent hues. To investigate the degradation processes that are occurring, five micro-samples were collected from different fluorescent-coloured areas and analysed by a combined approach based on µ-Raman and Surface Enhanced Raman Spectroscopy (SERS), High Performance Liquid Chromatography coupled with Diode Array Detector and mass spectrometry (HPLC-DAD and HPLC-MS), and Pyrolysis Gas Chromatography coupled with Mass Spectrometry (Py-GC-MS). The analytical protocol applied allowed us to disclose the painting materials used by the artist and fully characterise the ageing phenomena occurring in the mural that are possibly responsible for its colour ephemerality.